2017
DOI: 10.1097/j.pain.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Most red flags for malignancy in low back pain guidelines lack empirical support: a systematic review

Abstract: Clinicians do not want to miss underlying serious pathology, but it is still unclear which red flags are relevant. We aimed to evaluate the origin and evidence on diagnostic accuracy of red flags for malignancy for management of low back pain (LBP) in primary care. We performed a comprehensive overview and searched the literature using snowballing techniques and reference checking for evidence on red flags endorsed in clinical guidelines for identifying patients with higher likelihood of malignancy. We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 52 publications
3
41
0
4
Order By: Relevance
“…The very low specificity of most “red flags” contributes to unnecessary specialist referrals and imaging [30] , [31] . The “red flag” with the highest post-test probability for detection of spinal malignancy is the history of malignancy, and it has been noted that a “history of malignancy” and “strong clinical suspicion” are the only red flags with empirical evidence of acceptably high diagnostic accuracy [32] , [33] .…”
Section: Current Position Of the American College Of Physicians Amermentioning
confidence: 99%
“…The very low specificity of most “red flags” contributes to unnecessary specialist referrals and imaging [30] , [31] . The “red flag” with the highest post-test probability for detection of spinal malignancy is the history of malignancy, and it has been noted that a “history of malignancy” and “strong clinical suspicion” are the only red flags with empirical evidence of acceptably high diagnostic accuracy [32] , [33] .…”
Section: Current Position Of the American College Of Physicians Amermentioning
confidence: 99%
“… 42 In low back pain literature, a “strong clinical suspicion” has recently been reported as having acceptably high diagnostic accuracy as a red flag for malignancy. 43 We were not able to retrieve literature mentioning such a specific manner to diagnose bruxism. Therefore, we suggest that the extent of using this approach in bruxism diagnostics, and its validity be further researched.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 systematic review of 33 publications that included 13 different red flags endorsed by 16 guidelines found that a history of malignancy and high clinical suspicion were the only 2 red flags of 7 with acceptable diagnostic accuracy for malignancy. 6 Of the 33 publications, the studies that evaluated the 7 signs and symptoms with the most acceptable diagnostic accuracy showed moderate quality evidence. The positive likelihood ratios for diagnostic accuracy of malignancy were reported to range from 6.4 to 15.3 for history of malignancy and 12 to 54.2 for high clinical suspicion.…”
Section: Review Of Evidencementioning
confidence: 99%